If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 3r = -2(-3 + r) -4 + 3r = (-3 * -2 + r * -2) -4 + 3r = (6 + -2r) Solving -4 + 3r = 6 + -2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '2r' to each side of the equation. -4 + 3r + 2r = 6 + -2r + 2r Combine like terms: 3r + 2r = 5r -4 + 5r = 6 + -2r + 2r Combine like terms: -2r + 2r = 0 -4 + 5r = 6 + 0 -4 + 5r = 6 Add '4' to each side of the equation. -4 + 4 + 5r = 6 + 4 Combine like terms: -4 + 4 = 0 0 + 5r = 6 + 4 5r = 6 + 4 Combine like terms: 6 + 4 = 10 5r = 10 Divide each side by '5'. r = 2 Simplifying r = 2
| 1.3(7x+4)=1.8-(x+5) | | 4/7=-8v | | 7y^2+12y=y^2 | | 2xb=-1 | | -6p+4p=4(1+2p)-8(2+5) | | 2x^2+xy+y^2=16 | | -6+4p=4(1+2p)-8(2+5) | | 0=x^2+35x+750 | | x^1=-245 | | 4x^3+x-3=0 | | 6(2t+1)=3(7t+7) | | (k-75)/5=0 | | 4xb=1 | | (5x^2+4)*(6x-2)= | | x(8x+1)=3x^2-3x+1 | | 4/5x-15/4x=5/2 | | (y-6)-(y+8)=9y | | 5(x-6)=65 | | (6y-7)-(3y-5)*6=40 | | 10+0.10b=0+0.35b | | -6x-8=-7x+2 | | 8-9x-2=75+7x-15 | | -.4x+.5x+3=2 | | (y-6)-(y-8)=9y | | (2-x)(x+5)=0 | | .4x+.5x+3=2 | | 2x-40+x+x+60=900 | | 3x+12=9x-5(x+1) | | 11x+6y=-18 | | (2x+24)+y=180 | | 1.7=.25x+.1(x+3) | | 10-9x=52 |